2019
DOI: 10.3389/fpsyg.2019.01628
|View full text |Cite
|
Sign up to set email alerts
|

Research Review on Teacher Emotion in Asia Between 1988 and 2017: Research Topics, Research Types, and Research Methods

Abstract: Background: Studies on teacher emotion have steadily become more prominent. However, it has been observed that scholarship on teacher emotion has been dominated by contributions from Western societies. In the absence of a critical mass of empirical research generated from within the region such as Asia, lack of knowledge and capacity to inform policy and practice in teacher education and evaluation mechanism. Methods: The current study sought to mirror the patterns of knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 68 publications
0
24
0
8
Order By: Relevance
“…Teacher leadership has gained prominence for its potential to address increasing accountability while building sustainable learning capacity and professional growth (Crawford 2019 ). The multiple demands which flow almost endlessly into teacher leaders’ workplaces touch every aspect of their lives, which are flooded by emotions (Chen 2019a ). Moreover, as of 15 April 2020, the COVID-19 global pandemic has fundamentally disrupted schooling, affecting around 1.6 billion school-aged children in 191 countries worldwide (Lucas et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Teacher leadership has gained prominence for its potential to address increasing accountability while building sustainable learning capacity and professional growth (Crawford 2019 ). The multiple demands which flow almost endlessly into teacher leaders’ workplaces touch every aspect of their lives, which are flooded by emotions (Chen 2019a ). Moreover, as of 15 April 2020, the COVID-19 global pandemic has fundamentally disrupted schooling, affecting around 1.6 billion school-aged children in 191 countries worldwide (Lucas et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested to provide EFL teachers the knowledge and materials necessary to implement EBLI in their classes by preservice/in-service teacher training programs, as well as teacher training courses (TTC). Furthermore, recent studies have indicated that EFL teachers' emotions are directly related to their teaching success (Chen, 2019); therefore, it is recommended to make teachers aware of the benefits of critically and reflectively investigation of their emotional experiences during teaching experiences and seek ways to raise their emotional competencies. Likewise, it is suggested to make learners aware of the advantages of emotion regulation, EQ, emotioncy of vocabularies, and reflectivity to maximize learner engagement with language learning (Davoudi & Heydarnejad, 2020) and upgrade the final outcome.…”
Section: Discussionmentioning
confidence: 99%
“…La posibilidad de que ocurran intercambios de significados entre docentes y estudiantes, base del aprendizaje significativo, requiere de un intenso proceso afectivo (Cornejo, 2012;Martínez, 2007). Estas dimensiones emocionales de la docencia ocupan un lugar central en la agenda de investigación de las últimas dos décadas, particularmente respecto a las relaciones con sus estudiantes (Chen, 2019;Cornejo et al, 2020;Fried et al, 2015;Pekrun y Linnenbrink-Garcia, 2014;Sutton y Wheatley, 2003;Uitto et al, 2015).…”
Section: Introductionunclassified